Improving Students' Learning Motivation in Memorizing Hadith through the Use of Hadith Card Media at MI Ma'arif Pucungbedug - Khamimah; Khodriyah (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to analyze the effectiveness of the use of hadith card media in increasing students' learning motivation in memorizing hadith at MI Ma'arif Pucungbedug. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. Data from this study were obtained from a series of semi-structured interviews with the research subjects. The population of this study includes all individuals who have an important role in the learning process. The sample of the study consisted of one Al-Qur'an Hadith subject teacher and 10 fifth grade students selected based on the purposive sampling method. The results of the study showed that the use of hadith card media was proven effective in increasing students' learning motivation in memorizing hadith at MI Ma'arif Pucungbedug. In addition, card media has the potential to be applied to other appropriate subjects. The results of the study showed that hadith card media can improve student learning outcomes in learning the Qur'an and Hadith. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 58.71%, the first cycle 76.39% and in the second cycle increased to 93.66%. Thus, the use of hadith card media can be used as an alternative to improve student learning outcomes in learning the Qur'an and Hadith.